Predictive risk factors for liver abscess rupture: A prospective study of 138 cases - Ndong A; Tendeng JN; Ndoye NA; Diao ML; Dieye A; Diallo AC; Mansouri MR; Dia DA; Nibogora J; Fall F; Sagna SA; Konta B; et al. (Archives of Clinical Gastroenterology - Peertechz Publications, 2020)
Introduction: Liver abscess is a serious condition due to its complications. The most frequent complication is rupture. Our aim is to determine the predictive risk factors of liver abscess rupture at the Saint Louis Regional Hospital Center. Material and methods: This is a prospective descriptive and analytical study over the period of 1st January 2016 to 28th February 2019. We included liver abscess records regardless of age. An univariate and then multivariate analysis according to a Cox model allowed us to determine the factors associated with the occurrence of rupture. Results: We collected 138 cases with 78 cases of amoebic abscess (55.3%) and 60 cases of pyogenic abscess (42.6%). We had 36 cases of rupture (26%), including 29 cases in the peritoneal cavity. The mean age was 28 years ± 18. The sex ratio (M:F) was 3.7. There were 35.5% (n= 49) of patients aged under 15 years. The mean consultation time was 18.8 days ± 4.5. The localization was the right lobe in 76.7%, the left lobe in 9.3% and bi lobar in 14%. The mean diameter of abscesses was 8 cm ± 7.5 (Range: 3.7; 16 cm). The abscesses were unique in 85.5% of cases, and sub-capsular in 15.2% of case. Gas was present in 5.7% of cases. The commonest germ found was Staphylococcus aureus in 14.5% of patients. The predictive risk factors of rupture found after univariate analysis were: diameter (p <0.001), age less than 15 years (OR= 4.3; p<0.001), pyogenic origin of abscesses (OR= 4.3, p <0.001), undernutrition (OR=2.3, p= 0.038), jaundice (OR = 4.5, p = 0.009) , left-lobe localization (OR= 7, p = 0.002), subcapsular localization (OR=8.6, p <0.001); the presence of gas (p <0.001). Multivariate analysis identified 5 variables considered as independent risk factors for rupture: the pyogenic origin (HR= 22.51, p<0.001); age less than 15 years (HR= 2,296, p= 0.049); abscess diameter (HR= 1.411, p= 0.004); left lobe localization (HR= 18.68, p <0.001) and sub-capsular localization (HR= 2.689, p= 0.017). Conclusion: In our study, predictive risk factor for liver abscess rupture were: pyogenic origin, age less than 15 years, abscess diameter, left-lobe and subcapsular localization. The knowledge of these factors allows early and appropriate treatment to avoid complications.